Indications, Findings and Complications of Endoscopic Retrograde Cholangio-Pancreatograpghy (ERCP); A Study Conducted on the Patients Admitted in a Tertiary Care Hospital - Muhammad Ayub Naich, Sagheer Hussain, Romaiza, Hina Zamir, Adeel Qamar, Fatima Cheema, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To highlight the significance of endoscopic retrograde cholangio-pancreatography, its indications, findings and complications. Material and methods: This is a prospective study conducted on the patients admitted in the gastroenterology department of Sir Ganga Ram Hospital Lahore. Study period was of six months from July 2021 to December 2021. Main outcomes in this study were technical safety, indications of ERCP and complications. Study sample was calculated using WHO sample size formula. Results: Total 200 cases were included in this study including 116 (58%) male and 84(42%) female. CBD cannulation was done in 184(192%) cases. CBD stone was found in 35(17.5%), CBD stricture in 44(22%) and CBD stricture with stone found in 17(8.5%) cases. 11(5.5%) cases developed acute pancreatitis out of which 2(01%) cases had severe pancreatitis with collection of fluid. One case (0.5%) had retroperitoneal perforation which was managed conservatively. 03(1.5%) cases had bleeding after the procedure and hemostasis achieved by re-scope with adrenal injection at the bleeding point. Conclusion: ERCP procedure has a high success rate with minimum complications. Keywords: ERCP, Findings, Complications, CBD stone, Pancreatitis